COMPETITIVE ACTIVITIES AS A MECHANISM FOR HUMAN RESOURCES IDENTIFICATION AND DEVELOPMENT - Inna A. Gazieva (Высшее образование в России)
Abstract. This article actualizes the need to develop and implement a mechanism to identify the organization staff capacity, to its diagnosis and professional development. The article describes the experience of the Institute of organizational development and strategic initiatives of The Russian Presidential Academy of National Economy and Public Administration, which shows the effective use of such an approach. In particular, we are talking about the RANEPA best practices competition. This is a set of educational activities with a competitive component designed to identify, support and promote the best technologies and practices in the implementation of educational technologies, career management, intellectual property, their dissemination among the departments and branches of the Academy. The article presents the results of frequency analysis of the author’s opinion poll, the results of factor and cluster analysis, showing the difference in the level of development of the professional capacity of the respondents. The study results confirmed the effectiveness of the Competition as an approach for identifying and human resources development and the possibility of its use in practical activities of other organizations.